2017
DOI: 10.1074/jbc.m117.777029
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal half of transportin SR2 interacts with HIV integrase

Abstract: The karyopherin transportin SR2 (TRN-SR2, TNPO3) is responsible for shuttling specific cargoes such as serine/arginine-rich splicing factors from the cytoplasm to the nucleus. This protein plays a key role in HIV infection by facilitating the nuclear import of the pre-integration complex (PIC) that contains the viral DNA as well as several cellular and HIV proteins, including the integrase. The process of nuclear import is considered to be the bottleneck of the viral replication cycle and therefore represents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 72 publications
(91 reference statements)
0
22
0
Order By: Relevance
“…However the exact mechanism of action of TNPO3 still remains a matter of controversy [38]. Some studies suggest that TNPO3 participates in the nuclear import of PICs [9,25,39,40] whereas other authors propose that TNPO3 promotes HIV-1 infection though the interaction with HIV-1 CA [4143] or indirectly through the interaction of CPSF6 with HIV-1 CA [12]. Besides an indirect role for TNPO3 in viral integration through its interaction with CA and/or the IN and their respective cellular partners such as CPSF6 or LEDGF/p75 [38] has been proposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However the exact mechanism of action of TNPO3 still remains a matter of controversy [38]. Some studies suggest that TNPO3 participates in the nuclear import of PICs [9,25,39,40] whereas other authors propose that TNPO3 promotes HIV-1 infection though the interaction with HIV-1 CA [4143] or indirectly through the interaction of CPSF6 with HIV-1 CA [12]. Besides an indirect role for TNPO3 in viral integration through its interaction with CA and/or the IN and their respective cellular partners such as CPSF6 or LEDGF/p75 [38] has been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Several cellular import factors, including importin-7, importin-α3 and Transportin 3 (TNPO3, also called TRN-SR2) have also been involved in HIV-1 nuclear import [8]. Apart from its implication in nuclear import of the viral PIC, it has been confirmed that N-terminal end of TNPO3 protein act as a direct binding partner of HIV-1 IN [9]. Interaction with the viral CA has also been documented [10,11] and nearly 30 CA-mutants able to modify HIV-1 dependence on TNPO3 have been described [12].…”
Section: Introductionmentioning
confidence: 99%
“…Cellular proteins interacting with the PIC include the barrier to autointegration factor 1 (BAF1), high mobility group proteins (HMG), lamina-associated polypeptide 2α (LAP2α), lens-epithelium-derived growth factor (LEDGF/p75), and the karyopherin transportin SR2 (TRN-SR2, TNPO3). TNPO3 binds directly to the CCD and CTD of IN [ 149 ] and may participate in shuttling the PIC to the nucleus. The size of the PIC is uncertain, but it must fit through the nuclear pore, and the process of import is essential yet remains unclear.…”
Section: Integration: the Central Event In Hiv Replicationmentioning
confidence: 99%
“…Taken together, these results suggest that the major points of contact are the Gag MA region and the TNPO3 NPC binding domain, although it is important to note that other regions of Gag and TNPO3 appear to be required for maximal binding to occur. A recent study demonstrated that the N-terminus of TNPO3 (containing the RanGTP binding domain and part of the NPC interaction domain) interacts with the catalytic core domain and C-terminal domain of HIV-1 integrase, suggesting that other retroviral cargoes of TNPO3 bind to sites outside of the CBD (49).…”
Section: Discussionmentioning
confidence: 99%